BioSim Incubator: A Non-Biological Egg Incubation Simulation Platform - Rasmidatta, Rapinpa; Sooraksa, Pitikhate (My University, 2025)
This study presents the design, development, and evaluation of a BioSim incubator that integrates IoT-based environmental control with a biosimulation framework for predicting embryo development. The system employed an ESP8266 microcontroller, an SHT30 sensor, and a Node-RED/MQTT architecture to enable the real-time monitoring, automated actuation, and feedback control of temperature, humidity, and airflow. Experimental trials replicated the two key incubation stages: the development stage (Days 1-18, 37.5 ± 0.2 °C, 50-55% RH) and the lockdown stage (Days 19-21, 37.5 ± 0.2 °C, 65-70% RH). Results showed that the incubator maintained stable conditions within biologically favorable ranges, with only minor fluctuations that were rapidly corrected by the control logic. Comparison with practical risk guidelines indicated that the incubator’s performance corresponded predominantly to the “guaranteed survival” zone. To extend evaluation beyond environmental parameters, a virtual embryo feedback system was implemented as part of the BioSim framework, mapping deviations in temperature and humidity to predicted biological outcomes, which consistently indicated healthy chick development. In addition to demonstrating technical feasibility, the BioSim incubator provides a safe and accessible tool for STEM education and training, allowing students to study the relationship between environmental control and biological development without the use of live eggs.
Keywords: BioSim; egg incubation; non-biological egg; simulation platform